The Roll, the Codex, the Wax Tablet and the Synoptic Problem - Poirier, John C. 1963- (2012)
The Farrer hypothesis, especially as defended by Michael Goulder, has often been faulted for its supposed reliance on an anachronistic and technically impracticable understanding of Luke’s compositional practices. A closer look at the arguments against Farrer and Goulder, however, reveals a number of problems with this charge, including (but not limited to) its dependence on an inadequate understanding of how works were actually composed in antiquity. Goulder’s suggestion that Luke worked backwards through Matthew, in particular, has received a certain amount of criticism, but that scenario is shown here to be both technically feasible and perfectly in keeping with the way the ancients sometimes worked. Perhaps the greatest problem with the arguments made against the Farrer hypothesis is that they ignore Luke’s likely use of the wax tablet as a compositional aid—a medium that would have allowed Luke to rearrange Matthew’s material as freely as Farrerians suppose.
Keywords: wax tablets; Robert Derrenbacker; F. Gerald Downing; Michael Goulder; Synoptic Problem